THE DEPICTION OF HOMOSEXUALITY IN AMERICAN MOVIES - Rudy Rudy (Humaniora, 2016)
This study focuses on the depiction of homosexuality in American films. It is intended to identify the images of gays depicted in American films as well as the characteristics of American gay movies. It incorporates library research by applying an analytical descriptive approach in analyzing the data. The symbol and reflective theory is used to analyze 18 American movies and 14 gay films from other countries in the early 2000s. It shows that gay films can attract audiences by describing gays as the objects for laughs; gays revealing their sexual identities; sexual scenes of gays; masculine gay men; and violence in gay life. They appear in genres like drama, comedy, romance, detective, western, and horror/mystery with two images of gay people shown in American gay movies; they are the portrait of gays as a minority and the pessimism. However, it also shows that some American gay films picture good gay life, happy gay couples, gay marriage, etc.